Innovation in Educational Leadership: Global Theory, Global Research, Global Practice. - Magno, Catherine (2009)
Keywords: dept.edl; faculty_collection; sabbatical_report

A Handbook of Statistics and Quantitative Analysis for Educational Leadership - Mulcahy, John W. (University Press of America, 2009)
This handbook is an approachable reference for all levels of educational leadership. The topics are presented with a clarity that makes the mathematics accessible, even if the reader has not had prior training in research methods or statistics.
Keywords: School management and organization; Statistical methods; Statistical methods; Educational leadership; dept.edl; faculty_collection

Curriculum Alignment: Research-Based Strategies for Increasing Student Achievement - Squires, David A. (Corwin Press, 2009)
Keywords: Curriculum planning; Standards; United States; United States; Education; United States; Educational accountability; United States; Educational tests and measurements; dept.edl